GRPR-targeting radiotheranostics for breast cancer management - D’Onofrio, Alice; Engelbrecht, Swantje; Läppchen, Tilman; Rominger, Axel; Gourni, Eleni (Frontiers in Medicine, 2023)
Breast Cancer (BC) is the most common cancer worldwide and, despite the advancements made towards early diagnosis and novel treatments, there is an urgent need to reduce its mortality. The Gastrin-Releasing Peptide Receptor (GRPR) is a promising target for the development of theranostic radioligands for luminal BC with positive estrogen receptor (ER) expression, because GRPR is expressed not only in primary lesions but also in lymph nodes and distant metastasis. In the last decades, several GRPR-targeting molecules have been evaluated both at preclinical and clinical level, however, most of the studies have been focused on prostate cancer (PC). Nonetheless, given the relevance of non-invasive diagnosis and potential treatment of BC through Peptide Receptor Radioligand Therapy (PRRT), this review aims at collecting the available preclinical and clinical data on GRPR-targeting radiopeptides for the imaging and therapy of BC, to better understand the current state-of-the-art and identify future perspectives and possible limitations to their clinical translation. In fact, since luminal-like tumors account for approximately 80% of all BC, many BC patients are likely to benefit from the development of GRPR-radiotheranostics.